Is individual consistency in body mass and reproductive decisions linked to individual specialization in foraging behavior in a long‐lived seabird?. Issue 13 (8th June 2016) - Dehnhard, Nina; Eens, Marcel; Sturaro, Nicolas; Lepoint, Gilles; Demongin, Laurent; Quillfeldt, Petra; Poisbleau, Maud
Abstract: Individual specialization in diet or foraging behavior within apparently generalist populations has been described for many species, especially in polar and temperate marine environments, where resource distribution is relatively predictable. It is unclear, however, whether and how increased environmental variability – and thus reduced predictability of resources – due to global climate change will affect individual specialization. We determined the within‐ and among‐individual components of the trophic niche and the within‐individual repeatability of δ 13 C and δ 15 N in feathers and red blood cells of individual female southern rockhopper penguins ( Eudyptes chrysocome ) across 7 years. We also investigated the effect of environmental variables (Southern Annular Mode, Southern Oscillation Index, and local sea surface temperature anomaly) on the isotopic values, as well as the link between stable isotopes and female body mass, clutch initiation dates, and total clutch mass. We observed consistent red blood cell δ 13 C and δ 15 N values within individuals among years, suggesting a moderate degree of within‐individual specialization in C and N during the prebreeding period. However, the total niche width was reduced and individual specialization not present during the premolt period. Despite significant interannual differences in isotope values of C and N and environmental conditions, none of the environmental variables were linked to stable isotope values and thus able to explain phenotypic plasticity. Furthermore, neither the within‐individual nor among‐individual effects of stable isotopes were found to be related to female body mass, clutch initiation date, or total clutch mass. In conclusion, our results emphasize that the degree of specialization within generalist populations can vary over the course of 1 year, even when being consistent within the same season across years. We were unable to confirm that environmental variability counteracts individual specialization in foraging behavior, as phenotypic plasticity in δ 13 C and δ 15 N was not linked to any of the environmental variables studied. Abstract : Southern rockhopper penguins ( Eudyptes chrysocome ) show individual specialization in their foraging behavior only during certain parts of their annual life cycle. Individual specialization occurs during the prebreeding period, but is independent of body mass, timing of or investment into egg laying. During premolt, southern rockhopper penguins are typical food generalists.